Ultrasound examination of hemodynamic changes in patients with hepatitis (Texas Journal of Medical Science, 2022)
This research was aimed to evaluate portalsystemic hemodynamic changes in chronic severe hepatitis. Hemodynamic parameters included portal vein diameter, portal vein peak velocity, portal vein volume, spleen length, spleen vein diameter, spleen vein volume and umbilical vein recanalization. They were measured by color doppler ultrasonography in 30 patients with chronic severe hepatitis, compared with 40 normal controls, 25 patients with chronic hepatitis B, 30 patients with compensable cirrhosis, and 25 patients with decomposable cirrhosis.